Decay of Temperature Fluctuations in Homogeneous Turbulence before the Final Period for the Case of Multi-Point and Multi-Time in a Rotating System (Bangladesh Journal of Scientific and Industrial Research, 2007)
Using Deisslers approach the decay of temperature fluctuations in homogeneous turbulence before the final period for the case of multi-point and multi-time in a rotating system in presence of dust particle is studied and have considered correlation between fluctuating quantities at two and three point. Two and three point correlation equations in a rotating system is obtained and the set of equations is made to determinate by neglecting the quadruple correlations in comparison to the second and third order correlations. The correlations are converted to spectral form by taking their Fourier transforms. Finally integrating the energy spectrum over all wave numbers, the energy decay law of temperature fluctuations in homogeneous turbulent before the final period for the case of multi-point and multi-time in a rotating system is obtained. Bangladesh J. Sci. Ind. Res. 41(3-4), 147-158 2006